Концепции космотеории - Суворов, Н.П.; Суворова, И.Г. (Медична гідрологія та реабілітація, 2006)
Дана публікація є продовженням викладу авторського погляду на стратегію розвитку людини. The present publication defines the strategy of the evolutional development of the person and gives scientifically grounded to essence of the aristoV anqrwpoV (the aristocratic person).